2006
DOI: 10.1021/ja057306w
|View full text |Cite
|
Sign up to set email alerts
|

A New Ru-Catalyzed Cascade Reaction Forming Polycyclic Cyclohexadienes from 1,6-Diynes and Alkenes

Abstract: Functionalized bicyclic 1,3-cyclohexadienes can be easily prepared by a new cascade reaction which involves the Ru-catalyzed addition of acyclic alkenes to 1,6-diynes to give (Z)-hexatrienes, followed by a pure thermal 6e-pi electrocyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(23 citation statements)
references
References 10 publications
1
21
0
1
Order By: Relevance
“…[6] As a further contribution to the above methodology, we recently described a new "formal" [2+2+2] cycloaddition of terminal 1,6-diynes 1 with acyclic alkenes 2 in the presence of 10 % of an equimolar amount of [RuA C H T U N G T R E N N U N G (CH 3 CN) 3 Cp*]PF 6 (Cp* = pentamethylcyclopentadienyl) and Et 4 NCl to give 1,3-cyclohexadienes 4 (Scheme 2). [7] We also found that cyclic alkenes 5 reacted with diynes 1 to afford tricyclic cyclohexadienes 6 (Scheme 3). [7] Unlike their acyclic alkene analogues 2, the double bonds in cyclohexadienes 6 are in the position expected for a [2+2+2] cycloadduct (as observed by Itoh).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…[6] As a further contribution to the above methodology, we recently described a new "formal" [2+2+2] cycloaddition of terminal 1,6-diynes 1 with acyclic alkenes 2 in the presence of 10 % of an equimolar amount of [RuA C H T U N G T R E N N U N G (CH 3 CN) 3 Cp*]PF 6 (Cp* = pentamethylcyclopentadienyl) and Et 4 NCl to give 1,3-cyclohexadienes 4 (Scheme 2). [7] We also found that cyclic alkenes 5 reacted with diynes 1 to afford tricyclic cyclohexadienes 6 (Scheme 3). [7] Unlike their acyclic alkene analogues 2, the double bonds in cyclohexadienes 6 are in the position expected for a [2+2+2] cycloadduct (as observed by Itoh).…”
Section: Introductionmentioning
confidence: 85%
“…[7] We also found that cyclic alkenes 5 reacted with diynes 1 to afford tricyclic cyclohexadienes 6 (Scheme 3). [7] Unlike their acyclic alkene analogues 2, the double bonds in cyclohexadienes 6 are in the position expected for a [2+2+2] cycloadduct (as observed by Itoh). [6f,g] Our mechanistic hypothesis for the Ru-catalyzed reaction of diynes and alkenes involves two possible pathways, depending on the alkene used (Scheme 4).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The whole cascade process could be considered as a ''formal" [2+2+2] cycloaddition of alkynes to alkenes [24].…”
Section: Cprucl-catalyzed [2+2+2] Cycloaddition Of Alkynes To Alkenesmentioning
confidence: 99%
“…This process involves the [2+2+2] dimerization of the starting ortho-ethynylstyrene (1 a, a 1,5-enyne) instead of the expected Dixneuf product, the 1,4-diaryldiene 3 a, derived from head-to-head dimerization of arylacetylenes 1 with trapping of MeOH [Scheme 1, Eq. [11] The ruthenium-catalyzed dimerization of 1 a was optimized by systematically changing the reaction parameters (Table 1). [9] Even more strikingly, aromatization to naphthalene (4) was not detected in this case, despite it being the thermodynamically favored product often observed on reacting 1,5-arenynes 1 in the presence of other Ru II catalysts [Scheme 1, Eq.…”
mentioning
confidence: 99%